THE USAGE OF PHRASEOLOGICAL AND IDIOMATIC UNITS IN THE NOVEL "THE WHITE SHIP" BY CHINGIZ AITMATOV - Khabibulloyeva Gulchekhra Komiljonovna; Khabibulloyeva Sohiba Komiljon kizi (The Conference Hub, 2025)
In this article, several idioms and phraseological units of Kyrgyz culture are given. Catching and using these idioms or phrases can be challenging for foreigners, though there are some similarities and differences with any language. However, they are highly common, so, they are being translated into several foreign languages as well as English. There are some differences between colloquial and spoken languages as well as in a formal and formal styles. Sometimes, it is better to use equivalents, instead translate them, only we should pay attention to the meaning. Therefore, the meanings in two languages can be compared by many researchers and linguists. In this work, authors compared in both languages.
Keywords: nature, idioms, novel, ship, phrase, experience, meaning, tradition, culture.